Plumage variation in the Planalto Woodcreeper (Dendrocolaptes platyrostris) and the melanocortin-1 receptor gene (MC1R) - Corso, Josmael (2013)
The Planalto Woodcreeper (Dendrocolaptes platyrostris) presents “pale” and “dark” plumage variants, which are distributed throughout the Cerrado and Caatinga, and throughout the Atlantic Forest, respectively. To understand the genetic nature of the plumage variation in the species, we partially sequenced the melanocortin-1 receptor (MC1R) gene, which is associated with melanic phenotypes in vertebrates. We found no correlation between variation at MC1R sequences and plumage color in D. platyrostris. Aminoacid sites that were correlated with variation in melanic plumage in other bird species were monomorphic in D. platyrostris. Our results suggested that MC1R seems not to be involved in controlling plumage variation in D. platyrostris.